Possibility of uranium deposits within the Warchha sandstone, Nilawahan Group (Lower Permian) of the Salt Range - Azizullah; Butt, M. Jamil; Rehman, Abdul; Naveed, Arshad (Journal of Himalayan Earth Sciences, 2004)
On the basis of studies so far undertaken, the area from Waraia in the east to Nurpur in the west has been selected for further exploration work. Phosphatic nodules are present throughout this strike of 25 km. Chemical U3O8 Within these phosphatic nodules varies from 430 to 1008 ppm with an over age of 719 ppm. Strong bleaching and uraniferous solution movements are present in Simbal, Chitti Dand and Matin areas. Color bandings and bleaching, due to uraniferous solution movements within the sandstone strata, indicate that some uranium deposit was formed in the vicinity of Moregangh and Matin area, which has been effaced due to block faulting resulted by the Salt Range Thrust. Therefore, areas of high radioactivity, bleaching, color bandings and relatively higher chemical value of U3O8 need attention for further exploration. Both within the sandstone as well as in the phosphatic nodules, such as Simbal, Karuli, Moregangh and Matin area.